THE FATHERHOOD AFFAIR - Darcy, Emma; Mills & Boon Classics (Sydney, New South Wales : HarperCollins Publishers, 2024)
Damien Chandler wants a child! He thinks Natalie Hayes will make the ideal mother. Natalie Hayes wants a child! She just can’t picture Damien Chandler in the role of father. Natalie has tried not to think of Damien as anything but a business acquaintance, and she succeeds…until the night they share a bed! Damien has never been able to resist a challenge — now he faces the biggest challenge of his life. He has to convince Natalie that perfect lovers can become perfect parents, too!.
General
Keywords: Contemporary romance; Fiction - Romance - Contemporary; Electronic books